The Effectiveness of Cognitive Rehabilitation on Improving Academic Eemotions and Academic engagement of Students with Special Learning Disabilities in Girls' Secondary Period Schools in Rasht city - seyedeh zari noori; Seyedeh Maryam Mousavi (مطالعات روانشناسی تربیتی)
Difficulty in the desired academic emotions and reduced academic enthusiasm in students with special learning disabilities are common challenges that require increasing attention, and research on effective solutions is an undeniable necessity. The aim of the present study was to determine The Effectiveness of Cognitive Rehabilitation on Improving Academic Eemotions and Academic engagement of Students with Special Learning Disabilities in Girls' Secondary Period Schools in Rasht city. The research method was quasi-experimental with a pretest-posttest design with a control group. The statistical population of the research included all high school students with specific learning disabilities in girls' schools in Rasht city in the academic year of 2023-2024. Using the available sampling method, 30 students with special learning disabilities (15 in the experimental group and 15 in the control group) were selected and used as a pre-test they completed the questionnaires of academic emotions (Pekran et al., 2005) and academic engagement (Fredericks et al., 2004). Then, the experimental group underwent cognitive rehabilitation during 12 sessions of 60 minutes twice a week (Captain Log, 2020), while no intervention was implemented in the case of the control group; then both groups were subjected to post-test. The obtained data were analyzed using univariate and multivariate analysis of covariance. The findings of the research showed that cognitive rehabilitation is effective in improving positive academic emotions and components of pleasure and pride of students with special learning disabilities (P<0.01).